Water for Xalapa! Vicissitudes of the Xalapa City Council Facing the Supply of Drinking Water, Veracruz, México (1940-1945) - Rodríguez Gámez, Mariana (Revista de historia., 2023)
The supply of drinking water during the 1940s in the state of Veracruz was a slow process that reflected local governments’ slow improvement of urban infrastructure. In the case of Xalapa City, during the first five years of that decade, a series of issues related to the liquid occurred, denoting the precarious management and the attempt to improve the water infrastructure. In this sense, this article addresses the perception of the Xalapa city council regarding the project of «national modernity» through a content analysis of the municipal requests, specifically from the drinking water service to account for the council’s actions in this regard. Thus, reflecting from a local history perspective allows us to understand that urban processes are not unilateral in regional settings.